Escape into Creativity: Thoughts on the Margins of a New Work about Vasyl Stefanyk - Solovka, Liubov; Zhernokleiev, Oleh (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
Reviews - Velykochyi, V., Monolatii, I., & Derkachova, O. (2022). (Un)Expected Stefanyk. Brustury: Discursus.